Pertamina's Public Relations Communication Strategy in Dealing with the Plumpang Integrated Terminal Fire: Case Study of Corporate Crisis Communication in Dealing with Fire Victims - Rahim, Fachrulsyah Alif Mahendra; Bakti, Iriana; Sjoraida, Diah Fatma (Borong Newinera Publisher, 2024)
The fire incident at the Pertamina Plumpang Integrated Terminal that occurred in March 2023 was a disaster that resulted in casualties and losses for residents around Plumpang. The coverage of the Plumpang incident had a direct impact on the company's image and reputation. This is where public relations communication strategies play a role in restoring public trust as a form of post-disaster handling. The author uses descriptive qualitative analysis by applying issue life circle analysis to examine the findings regarding case handling. The research results show that the handling of the Plumpang Integrated Terminal fire tragedy crisis was carried out by adopting policies based on the results of discussions between Pertamina, affected residents and stakeholders, such as the program for creating an Integrated Information Post, the Sire Emergency Response program and the Emergency Training program. Handling efforts are divided into three stages, namely shor term strategy, with responsive handling through the Pertamina Peduli program, medium term, by building an Integrated Information Post, and long term, by conducting level 2 emergency simulation training. Pertamina's public relations communication strategy in handling The Plumpang Integrated Terminal fire tragedy was carried out through personal communication by holding discussions with community leaders related to the Integrated Information Post. Personal communication is also carried out by approaching residents, using empathy strategies to provide two-way communication while knowing the facts on the ground, conducting blusukan related to needs, complaints and desires in the event of the Plumpang Integrated Terminal fire tragedy.